Myricetin: targeting signaling networks in cancer and its implication in chemotherapy - Zeeshan Javed; Khushbukhat Khan; Jesús Herrera-Bravo; Sajid Naeem; Muhammad Javed Iqbal; Qamar Raza; Haleema Sadia; Shahid Raza; Munir Bhinder; Daniela Calina; Javad Sharifi-Rad; William C. Cho (Cancer Cell International, 2022)
Abstract The gaps between the complex nature of cancer and therapeutics have been narrowed down due to extensive research in molecular oncology. Despite gathering massive insight into the mysteries of tumor heterogeneity and the molecular framework of tumor cells, therapy resistance and adverse side effects of current therapeutic remain the major challenge. This has shifted the attention towards therapeutics with less toxicity and high efficacy. Myricetin a natural flavonoid has been under the spotlight for its anti-cancer, anti-oxidant, and anti-inflammatory properties. The cutting-edge molecular techniques have shed light on the interplay between myricetin and dysregulated signaling cascades in cancer progression, invasion, and metastasis. However, there are limited data available regarding the nano-delivery platforms composed of myricetin in cancer. In this review, we have provided a comprehensive detail of myricetin-mediated regulation of different cellular pathways, its implications in cancer prevention, preclinical and clinical trials, and its current available nano-formulations for the treatment of various cancers.